PENGARUH TEMAN SEBAYA TERHADAP ORIENTASI MASA DEPAN SISWA - Fitriani, Dwi; Masing, Musa (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2022)
Adolescents in the current development. requires peers to facilitate adolescents in determining future orientation after graduating from high school.The purpose of this study was to determine how much influence peers have on the future orientation of class XI science students in one of the public high schools in Manado city. Respondents in this study were 134 students of class XI science. In this study using a quantitative approach with correlation analysis techniques that are processed using SPSS 21.0 for windows. The data collection technique used an instrument in the form of a questionnaire with a system using a Likert scale model. Results based on data analysis, the influence of peers on future orientation by looking at the ANOVA test value is fcount = 9.920 > ftable = 3.84. From the results, if fcount>ftable, the hypothesis Ha in this study is accepted. The influence of peers on future orientation can be seen from the R2 value of 0.070. This means that peers have an influence of 7% on the future orientation of class XI science students